Sakralisasi VS Desakralisasi, Takhayul VS Rasionalisme Dalam Studi Sejarah Kesenian Berutuk Dari Desa Trunyan, Bali - Fisabil Mahardika Putra (Institut Seni Indonesia Yogyakarta, 2018)
This paper answer the question of what a Berutuk Art from the Trunyan village of Bali is seen from historic there the art was once very sacred, then how the implementation of art and why now that started from the year 1997 experienced desacralization. To answer questions, the research method used is literature study. The result of the research, the art of berutuk originally is a very sacred art, because it can bring prosperity that is realized with the coming rain. In the execution of art is played by a males who still virgin with an odd number, then two of them act as a Batara Berutuk and queen. Today the art of berutuk desacralization due to modernisation which refers to the approach of rationalism which is contrary to superstition or unreasonable.Keywords: the art of berutuk, execution, desacralization, modernization, rationalism, superstition